PO163 Improving the diagnosis of encephalitis through examining host proteome and gene expression. (1st December 2017) - Ellul, Mark; Griffiths, Michael; Hiscox, Julian; Solomon, Tom
Abstract : Encephalitis is a devastating neurological condition caused by either an acute infection or an autoimmune process, each requiring very different treatment. However in up to two thirds of cases the cause is unknown. This project aims to address the question: can the diagnosis of encephalitis be improved by using novel approaches to examine the host response? Aims and Objectives: 1. Using a whole proteome approach, examine the patterns of host inflammatory mediators in the CSF of patients with infectious and autoimmune encephalitis. 2. Explore host gene expression patterns in blood of the same patients. 3. Based on the above, determine the best markers to distinguish infectious from autoimmune encephalitis, and apply these to patients with encephalitis of unknown cause. Diagnostic algorithms will then be developed to distinguish the different aetiological groups, and applied to patients with encephalitis of unknown cause. The robustness of the approach will be tested by applying it prospectively to a new cohort of encephalitis patients. Scientific and Clinical Implications: This study will deliver new scientific insights on host responses in encephalitis, and importantly improve the diagnosis of those with unknown cause, thus allowing appropriate treatment to be started.